Ketrampilan Sosial dalam Kaulinan Huhuian: Kisah dari Indonesia - Susan Maulani (Jurnal Inovasi Pendidikan Dasar, 2019)
The notion about social skill often was ignored in elementary school because many teachers thought that students’ learning achievement was more important than skill development. This study tried to describe conceptually about social skill in kaulinan huhuian. The research method was case study. Six teachers of Elementary School from two different schools in Bandung City, West Java, Indonesia were selected as participant. Data was collected through semi structure interview and observation. Data analysis process by using grounding approach. The finding of this study showed that there were some social activities in kaulinan huhuian, namely deciding who become ucing, making formation like hui (sweet potatoes), sing kakawihan (song), and dialog between ucing and huiand. Social skill that can be developed was honesty, togetherness and the ability to interact with other people and the surrounding environment. This finding also can give solution to generate learning process whether model, strategy, technique which develop social skill in students.